1996
DOI: 10.1074/jbc.271.49.31312
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change of Cytochrome P450 1A2 Induced by Sodium Chloride

Abstract: Recently, it was reported that the activity of rabbit P450 1A2 is markedly increased at elevated sodium phosphate concentration. Here, the possible structural change of rabbit P450 1A2 accompanying the NaCl-induced increase in its enzyme activity is investigated by fluorescence spectroscopy, circular dichroism, and absorption spectroscopy. It was found that NaCl increased ␣-helix content and lowered ␤-sheet content of P450 1A2 in the presence as well as in the absence of a phospholipid. Intrinsic fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 31 publications
9
56
1
Order By: Relevance
“…In contrast, maximal EROD activity of the CYP1A2 system increased to a maximum at 200 mM HEPES and declined with further increases in buffer concentration. Declining activities with increasing buffer concentrations were expected and have been attributed to the disruption of electrostatic interactions between reductase and P450, consistent with previous studies (6)(7)(8)(9)(10)(11)(12)(13)(14)16,17,24,39). When comparing EROD in the mixed reconstituted system to the sum of the rates of the binary systems (which can be seen by comparing the third and fourth bars from each group), a significant synergistic stimulation of EROD was observed at lower ionic strength; higher concentrations of HEPES relieved this synergism.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, maximal EROD activity of the CYP1A2 system increased to a maximum at 200 mM HEPES and declined with further increases in buffer concentration. Declining activities with increasing buffer concentrations were expected and have been attributed to the disruption of electrostatic interactions between reductase and P450, consistent with previous studies (6)(7)(8)(9)(10)(11)(12)(13)(14)16,17,24,39). When comparing EROD in the mixed reconstituted system to the sum of the rates of the binary systems (which can be seen by comparing the third and fourth bars from each group), a significant synergistic stimulation of EROD was observed at lower ionic strength; higher concentrations of HEPES relieved this synergism.…”
Section: Resultssupporting
confidence: 91%
“…Kelley et al (2005) used high concentrations of buffer salts to eliminate any ionic interactions between CYP1A2-CYP2B4 and were able to regain most of the activity that had been diminished by the purported interactions. However, circular dichroism studies have demonstrated conformational changes in proteins at high salt concentrations (Yun et al, 1996), rendering the aforementioned studies somewhat ambiguous. It is possible that ionic interactions play a role in P450-P450 interactions but additional work in this area is needed.…”
Section: Effect Of Cpr On 1:1 Cyp2c9/cyp2d6-mediated (S)-flurbiprofenmentioning
confidence: 99%
“…For the assay, two different approaches were taken to examine the effect of phospholipid and detergent on the P450 1A2 activity using the method described elsewhere with slight modification (14). For the NADPH-P450 reductase-supported reactions, 0.5 nmol of P450 1A2, 0.6 nmol of NADPH-P450 reductase, 15 g of phospholipid or detergent, and an NADPH-generating system were mixed together.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that the stimulated activity of P450 1A2 by the high concentration of salt accompanies structural change of P450 1A2 in the presence of phospholipid (14). It seems worthwhile, therefore, to study the structural changes of P450 1A2 induced by phospholipid in detail to elucidate the relationship between the structure and the activity.…”
mentioning
confidence: 99%